Photoswitchable anapole metasurfaces - Wang, Wenhao (2022)
Nonradiating charge-current configurations have attracted attention in photonics for the efficient localization of the electromagnetic field. Anapole mode is a unique nonradiating state of light induced by the interference of electric and toroidal dipole that possesses rich physics with potential applications in micro-nanophotonics. Active control of an anapole is essential for the design and realization of tunable low-energy photonic devices. Here, an active anapole metasurface device is experimentally demonstrated as a switch for the terahertz waves. The metadevice consists of planar resonators with photoactive inclusions of silicon patches in a hybrid metal–semiconductor configuration. The active element enables dynamic control over the contributions of the multipoles that eventually determine the formation of the exotic anapoles that host extreme nonradiative confinement and its active switching into sub-radiative Fano resonance and highly radiative electric dipoles. Two orders of magnitude change in the near-field intensity of the anapole that leads to 201% extinction modulation is further demonstrated. The anapole metadevice provides a platform to efficiently control both the far-field radiation and near-field enhancement in metaoptics, promoting active micro-nanophotonic devices for potential applications in terahertz modulators, lasers, filters, and dynamic near-field imaging.